Using experience-based co-design to prioritise areas for improvement for patients recovering from critical illness. (June 2023) - Twamley, Jacqueline; Monks, Rob; Beaver, Kinta
Abstract: Objectives: Critical illness recovery is a journey; from intensive care unit to hospital ward to home. However, evidence is limited on how best to enable recovery from critical illness. This study aimed to prioritise areas for improvement in care and services for patients recovering from critical illness. Research design: This study used experience-based co-design. Service users and providers worked in partnership to identify and prioritise service improvements for patients who had survived an episode of critical illness. Method: Qualitative interviews were carried out with patients (n = 10) who had experienced critical illness, and staff (n = 9) who had experienced caring for patients in the intensive care unit. Key patient touchpoints were identified and used to produce a film, reflecting the critical illness journey. A patient feedback event incorporated an emotional mapping exercise, to identify key points during the recovery journey. A joint patient/family (n = 10) and staff (n = 10) event was held to view the film and identify priorities for improvements. Findings: Emotional mapping highlighted areas where services were not synchronised with patients' needs. Four patient-focussed priorities for service improvement emerged 1. Improving the critical care experience, 2. Addressing patients' emotional and psychological needs, 3. Positioning patients at the centre of services and 4. Building a supportive framework for recovery. Conclusion: Evidence-based co-design was used successfully in this study to identify priorities for improvements for patients recovering from critical illness. This approach positions patients at the centre of service improvements and realigns care delivery around what matters most to patients. Person-centred care provision underpins all identified priorities. Implications for clinical practice: Intensive care unit staff should get to know patients and their families by talking more to patients and families about their care and engaging in more non-medical conversations. Emotional and psychological support should be provided to aid rehabilitation and recovery from critical illness in the intensive care unit, on general wards, and in the community. Information and services should be available when patients need them, rather than at fixed time points or settings. Recovery services should focus on enabling and building the self-efficacy of patients to empower them to be in control of their recovery journey.